Re-Constructing Grassroots Holocaust Memory The Case of the North Caucasus - Rebrova, Irina (SpatioTemporality / RaumZeitlichkeit Ser., 2020)
Intro -- Acknowledgements -- Contents -- 1 Introduction -- 2 The Holocaust in the North Caucasus -- 3 (Re)writing Holocaust Memory in Official Soviet Wartime Sources -- 4 Memorial Sites: Re-framing Holocaust Memory -- 5 Depicting Jewish Fates: Artistic Responses to the Holocaust in the North Caucasus -- 6 Reifying Memory? Representations of North Caucasus Holocaust History in Museum Collections -- 7 We Don't Need No . . . Holocaust Education? -- 8 Revisiting Experience: Personal Narratives of the Holocaust in the North Caucasus -- 9 Conclusion. Key Features of the Holocaust Memory Dispositif -- Bibliography -- Tables -- List of Abbreviations -- Index.